Descriptive epidemiology of traumatic injuries during the first lockdown period of COVID-19 crisis in Iran: A multicenter study - Khak, M.; Shakiba, S.; Rabie, H.; Naseramini, R.; Nabian, M. H. (Asian Journal of Sports Medicine, 2020)
Background: The study of alterations in the epidemiological pattern of traumatic injuries during the COVID-19 crisis can provide estimates in the planning of healthcare resources. In a prospective epidemiological study during the first 45 days of lockdown legislation in Iran and by comparing the results with previously published large population-based studies in Iran, we sought changes in the epidemiology of traumas.